73.1: A Novel Pixel Structure for High Transmittance and High Image Quality LCDs. Issue 1 (June 2015) - Lee, Joon‐Dong; Lee, Jong‐Bum; Cho, Seong‐Joon; Yang, Joon‐Youn; Jun, Myungchul; Kang, InByeong; Yeo, Sang‐Deog
Abstract : We propose a new 2P2D pixel design which has a trapezoidal shape. for high transmittance and image quality.The pixel design facilitates a reduction of disclination area in the pixel and image defects. As a result, we have achieved 14% higher transmittance than the conventional AH5‐IPS and also a better image characteristic than the general 2P2D structure in 5inch HD LCD panels.